ANTIFUNGAL APPRAISAL OF BURKHOLDERIA GLADIOLI STRAIN VIMP03 (JQ867372) AGAINST CERATOCYSTIS PARADOXA - Mahamuni, Shrikumar V; Shinde, Nitin S; Wani, Prakash V; Patil, Ashok S (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: The purpose of the present investigation was to assess antifungal characterization of Burkholderia gladioli strain VIMP03 (JQ867372), an isolate from sugar beet rhizosphere. Methods: Antifungal characterization was carried out by biochemical, dual culture, and agar well diffusion methods against Ceratocystis paradoxa, a soilborne pathogen of sugarcane and other crops. Culture filtrate and ethyl acetate extract obtained from culture supernatant were analyzed by highperformance liquid chromatography (HPLC) and gas chromatography-mass spectrometry (GC-MS) analyses, respectively. Results: The culture filtrate and ethyl acetate extract exhibited effective antifungal activity. Organic acid profile of the culture filtrate was determined. Acetic acid was mainly produced by the culture under study. The GC-MS analysis of ethyl acetate extract documented the presence of compounds including tetratetracontane, 9-nonadecene, erucic acid, and other hydrocarbon derivatives. Conclusion: The GC-MS, HPLC, and biochemical profiles of B. gladioli strain VIMP03 (JQ867372) revealed its agro clinical-antifungal potential. Keywords: Antifungal, Burkholderia gladioli, High-performance liquid chromatography, Gas chromatography-mass spectrometry.